Evaluasi Pelaksanaan QCL Assembly di PT. XYZ dengan Mempertimbangkan Ketersediaan Waktu dan Jumlah Sampel - Jonathan Kristiadi Srikuning; Benedictus Rahardjo (Jurnal Titra, 2018)
The purpose of this study is to find out the total time required to perform the QCL (Quality Control Line) Assembly thoroughly and the exact number of samples for each checking element. The collected data is used to calculate the standard time for each checking element, where the total time required exceeds the time available. The shortage of time has reached 122.204 minutes and when the number of samples is adjusted with MIL STD 105E and MIL STD 414 then the shortage of time reaches 403.918 minutes. The proposed improvements are the minimization of the frequency of inefficient work elements, changes in details of check for non-critical elements, and the use of support personnel. These improvements have a positive impact, i.e. there is a remaining time of 18.433 minutes of total time available.